Current and new imaging techniques in risk stratification of asymptomatic severe aortic stenosis. Issue 4 (21st April 2022) - Kammoun, Ikram; Sghaier, Ahmed; Bennour, Emna; Laroussi, Lobna; Miled, Manel; Neji, Henda; Ben Halima, Afef; Addad, Faouzi; Marrakchi, Sonia; Kachboura, Salem
Abstract: Aortic stenosis (AS) is one of the most common valvular diseases in clinical practice. The prevalence of calcified AS with moderate or severe stenosis exceeds 2% after 75 years. The optimal timing of intervention for asymptomatic severe AS is uncertain and controversial. Identification of high-risk patients is based on echocardiographic parameters (left ventricular dysfunction, AS severity and progression), hemodynamic response to exercise, pulmonary hypertension, and elevated brain natriuretic peptides. However, early surgical aortic valve replacement (AVR), when compared to the watchful waiting approach, was associated with survival advantage. Moreover, new insights into pathophysiology of AS and advances in imaging modalities were helpful in the management of asymptomatic AS. In this report, we detail the potential role of echocardiography to guide timing of surgery and we discussed the use of early risk features based on recent imaging modalities.